Improving SDI Systems: Implications of New Retrieval Models - Rajashekar, T. B. (Journal of Information and Knowledge, 2014)
Any improvements in profile construction and processing procedures can have a marked impact on the overall performance of a SDI system serving a large user base. N.C.S.I. provides SDI service to more than 2000 scientists using the tape updates of five major science databases. The system works on inverted files using strict Boolean logic. Although well developed procedures for profile construction are available, major problems lie in the identification of important concepts, deciding their relative importance and establishing their relations. With a view to identify more simplified procedures, an experiment was conducted using Quorum logic. Profile construction was found to be quite easy but no marked improvemnets in processing and retrieval effectiveness could be made. A study of the Fuzzy-set, Probabilistic and Vector retrieval models was made to identify their important findings which have a bearing on the SDI systems. Some of these findings have been used to improve profile construction procedures at: N.C.S.I. Through a refined profile form users now contribute significantly to proper formulation of profile information. 30 to 40% reduction in profile construction title has been observed. Possibilities of a refined Quorum logic system for SDI and other improvements in profile processing are indicated.